2017
DOI: 10.1007/s00240-017-0992-z
|View full text |Cite
|
Sign up to set email alerts
|

Procedural sedation and analgesia for pediatric shock wave lithotripsy: a 10 year experience of single institution

Abstract: The aim of this study was to evaluate anesthesia practice for pediatric extracorporeal shock wave lithotripsy (ESWL) according to the age groups and discuss the anesthetic management of these patients. Pediatric patients treated with ESWL because of urolithiasis under anesthesia in our department between December 2007 and January 2017 were evaluated retrospectively. A total of 251 patients were divided into two groups as Group PS: preschool children (<6 years) and Group S: school children (≥6 years). Groups we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…It can be performed under anaesthesia, especially in the paediatric age group. 17 While there is an effective analgesia recommendation in the guidelines, there is no suggestion about anaesthesia. Movement and deep breathing excursion because of pain should be reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be performed under anaesthesia, especially in the paediatric age group. 17 While there is an effective analgesia recommendation in the guidelines, there is no suggestion about anaesthesia. Movement and deep breathing excursion because of pain should be reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In urology clinics, most ESWL procedures are performed without general anaesthesia or sedation. It can be performed under anaesthesia, especially in the paediatric age group 17 . While there is an effective analgesia recommendation in the guidelines, there is no suggestion about anaesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…Ketamine is one of the most commonly used anesthetics in sedation, anesthesia and analgesia during pediatric examination and surgical operation [4][5][6] . The studies in rodents, nonhuman primates and clinic suggest that the prolonged and/or repeated ketamine exposure during brain developmental period may evoke neuronal apoptosis and inhibit neurogenesis, leading to neurobehavioral abnormalities in the adulthood [7][8][9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Ketamine is widely used in analgesia and sedative processes during pediatric examination and surgical operation [1][2]. Recently, an increasing number of research have suggested that neonatal ketamine exposure could cause neuroapoptosis and disturb normal neurogenesis in the developing brain and increase the risk of delayed neurocognitive dysfunction [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%